2014
DOI: 10.3727/096368913x670921
|View full text |Cite
|
Sign up to set email alerts
|

Rat Mesenchymal Stem Cell Secretome Promotes Elastogenesis and Facilitates Recovery from Simulated Childbirth Injury

Abstract: Vaginal delivery is a risk factor for stress urinary incontinence (SUI). Mesenchymal stem cells (MSCs) home to injured organs and can facilitate repair. The goal of this study was to determine if MSCs home to pelvic organs after simulated childbirth injury and facilitate recovery from SUI via paracrine factors. Three experiments were performed. Eighteen female rats received vaginal distension (VD) or sham VD and labeled intravenous (IV) MSCs to investigate if MSCs home to the pelvic organs. Whole-organ imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 37 publications
5
65
0
Order By: Relevance
“…MSCs have also been induced to differentiate into a smooth muscle phenotype when exposed to conditioned media from smooth muscle cell cultures or when induced with specific myogenic growth factors for application to bladder reconstruction . More recent work, however, suggests a more complex role of stem cells in functional recovery, with some studies demonstrating that paracrine secretions of MSCs play an important role in the regeneration process [Carvalho et al 2011;Ranganath et al 2012;Dissaranan et al 2013].…”
Section: Stem Cell Differentiationmentioning
confidence: 99%
See 4 more Smart Citations
“…MSCs have also been induced to differentiate into a smooth muscle phenotype when exposed to conditioned media from smooth muscle cell cultures or when induced with specific myogenic growth factors for application to bladder reconstruction . More recent work, however, suggests a more complex role of stem cells in functional recovery, with some studies demonstrating that paracrine secretions of MSCs play an important role in the regeneration process [Carvalho et al 2011;Ranganath et al 2012;Dissaranan et al 2013].…”
Section: Stem Cell Differentiationmentioning
confidence: 99%
“…In addition, recent work investigating MSCs for SUI has shown that chemokine ligand 7 (CCL7), a homing factor for MSCs, is upregulated in both the urethra and vagina after vaginal distension (VD), suggesting that intravenously administered MSCs could have the potential to home to sites of injury in SUI [Woo et al 2007;Wood et al 2008;Lenis et al 2012]. Subsequent literature examining intravenous injection of MSCs in a VD rat model of simulated childbirth injury showed that MSCs home to the urethra and vagina and facilitate recovery of continence as measured by leak point pressure (LPP) [Cruz et al 2011;Dissaranan et al 2013]. Recent work by Lenis and colleagues used a rat model of childbirth injury with both virgin rats that had undergone VD and postpartum rats to further investigate the expression of chemokines and receptors involved in stem cell homing and tissue repair [Lenis et al 2013].…”
Section: Stem Cell Homingmentioning
confidence: 99%
See 3 more Smart Citations